THE USE OF GOOGLE FORM AS A FORMATIVE ASSESSMENT TOOL IN LEARNING PROCEDURE TEXT - Yuniar, Ainun Nisa; Wiyaka; Lestari, Siti (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2025)
Google Form is an application that can be used for free to assist teachers in assessing student learning outcomes in this modern era. This study aims to 1) To find out the use of Google Form as a formative assessment tool, 2) To find out students' perceptions of using Google Form as a formative assessment tool in Procedure Text learning and to find out the obstacles they face in using Google Form. The theory used to analyze the formulation of the problem was the behavioristic theory of Burrhus Frederic Skinner and Edward Lee Thorndike. Data collection methods used are interview, observation, and documentation. The data that has been collected was analyzed using a qualitative descriptive analysis method through data reduction, data presentation and making conclusions. The results showed that the use of Google Forms as a formative assessment tool in learning Procedure Text for tenth grade students of SMA Negeri 5 Semarang includes 3 stages : the preparation stage, the implementation stage, and the final stage. Students' perception of the application of Google Form as a formative assessment tool in learning Procedure Text were easy to use, flexible, and effective. However, the obstacles encountered in using Google Form were unstable internet connection and limited internet quota.